Nikolai S. Penn, a Man from Kuzbass (300th Anniversary of Kuzbass) - N. M. Morozov (Вестник Кемеровского государственного университета, 2021)
The article features the biography of Professor Nikolai S. Penn, who was the leading specialist in coal enrichment in Kuzbass in the 1930s – 1940s and a successful discoverer of coal deposits in Kuzbass and Eastern Siberia. At the Tomsk Institute of Technology, he organized the work of the mining department, edited scientific journals, and developed Siberian coal science. At the Kuznetsk Research Mining Institute (KuzNIUI, Novosibirsk, Prokopyevsk), N. S. Penn focused on the theoretical issues of coal origin and the mathematical analysis of coal, which made it possible to define coal components, washability, and type. The article also describes Prof. Penn’s personal qualities, as well as  achievements of his famous ancestors who were involved in some major events in the history of England and the United States.